(untitled) (Salud, Arte y Cuidado, 2018)
Delleman-Oorthuys syndrome, also called oculo-brain-cutaneous syndrome, is a rare congenital disorder, sporadic, with low prevalence of unknown etiology, characterized by cutaneous, ocular and cerebral malformations. The lesions are related to an incomplete closure of the embryonic fissure. It is reported, a new case of newborn, male patient, with Delleman-Oorthuys syndrome; who is referred to the Consultation of Medical Genetics for presenting mild psychomotor retardation, orbital cyst in the right eye, papulonodular lesions in the right lateral canthus, in both little fingers and neck. Findings are discussed, a bibliographic review is made, plus the patient’s clinic, compared with those found in other reports. The objective of this case is to specify an accurate diagnosis for the subsequent genetic counseling of the parents on the quality and life expectancy of the patient, as well as to contribute information to the national and international literature, since in Venezuela no other case has been reported